2007
DOI: 10.1083/jcb.200703157
|View full text |Cite
|
Sign up to set email alerts
|

Organization of chromatin and histone modifications at a transcription site

Abstract: According to the transcription factory model, localized transcription sites composed of immobilized polymerase molecules transcribe chromatin by reeling it through the transcription site and extruding it to form a surrounding domain of recently transcribed decondensed chromatin. Although transcription sites have been identified in various cells, surrounding domains of recently transcribed decondensed chromatin have not. We report evidence that transcription sites associated with a tandem gene array in mouse ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 34 publications
0
23
2
Order By: Relevance
“…It has been shown that actively transcribed DNA sequences at the ~2 Mbase mammary tumor virus (MMTV) array are extruded from transcription sites as highly decondensed domains not detected by conventional DNA FISH protocols (Muller et al, 2007). Although we failed to obtain any experimental evidence for extended loops, whether snoRNA gene arrays reflect the same chromatin configuration as MMTV array remains an open question.…”
Section: Discussioncontrasting
confidence: 43%
“…It has been shown that actively transcribed DNA sequences at the ~2 Mbase mammary tumor virus (MMTV) array are extruded from transcription sites as highly decondensed domains not detected by conventional DNA FISH protocols (Muller et al, 2007). Although we failed to obtain any experimental evidence for extended loops, whether snoRNA gene arrays reflect the same chromatin configuration as MMTV array remains an open question.…”
Section: Discussioncontrasting
confidence: 43%
“…When released after termination, a gene would still be near a factory and still carry the active histone modifications that could keep it in an open state, leading to efficient reinitiation (Bartlett et al 2006). In agreement with this concept, domains of decondensed and recently transcribed chromatin carry histone marks that are associated with active transcription (Muller et al 2007).…”
Section: Transcription Factoriesmentioning
confidence: 55%
“…BrUtP incorporation the protocol followed that in [67], with the following modifications. the permeabilization buffer contained 10 μg/ml instead of 25 μg/ml digitonin, dexamethasone was omitted.…”
Section: In Situ Hybridization and Immunostainingmentioning
confidence: 99%